2019
DOI: 10.1007/s40858-018-0271-8
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and altitudinal differences in coffee leaf rust epidemics on coffee berry disease-resistant varieties in Southwest Ethiopia

Abstract: Coffea arabica is native to the Afromontane forests of southwestern Ethiopia, the leading African country in Arabica coffee production. The intensity of coffee leaf rust (CLR), a fungal disease of growing concern to coffee farmers, was assessed in eight coffee berry disease-resistant C. arabica varieties planted at three different altitudes. Disease variables assessed were CLR prevalence (percent of infected plants), incidence (percent rusted leaves) and severity (percent leaf area affected) at four times with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 19 publications
1
27
0
1
Order By: Relevance
“…Changes in crop management practices during the last three decades have been linked to the emergence of CLR in Ethiopia, including the widespread use of high yielding but CLR-susceptible varieties grown in poorly managed plantation systems largely adopted at the lowlands (Jefuka et al 2010). Most notably, the effect of altitude which explained most of the variation in CLR intensity in our survey, was expected given its known effect on epidemic components such as infection efficiency and duration of the latency period (Bock 1962;Kushalappa 1989;Brown et al 1995;Daba et al 2018;Garedew et al 2019). Several studies conducted elsewhere, including Ethiopia, have…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…Changes in crop management practices during the last three decades have been linked to the emergence of CLR in Ethiopia, including the widespread use of high yielding but CLR-susceptible varieties grown in poorly managed plantation systems largely adopted at the lowlands (Jefuka et al 2010). Most notably, the effect of altitude which explained most of the variation in CLR intensity in our survey, was expected given its known effect on epidemic components such as infection efficiency and duration of the latency period (Bock 1962;Kushalappa 1989;Brown et al 1995;Daba et al 2018;Garedew et al 2019). Several studies conducted elsewhere, including Ethiopia, have…”
Section: Discussionmentioning
confidence: 64%
“…shown that CLR severity tends to decrease with the increase in altitude where the fields experience relatively lower night time temperatures (Wondimu 1991;Hindorf and Omondi 2011;Daba et al 2018;Garedew et al 2019). In Central America, prior to the epidemics recorded in Guatemala during the early 2010s, CLR was less likely to occur at production sites above 1,000 m, where cooler night and daytime conditions decreases infection efficiency and extends the latency period (Avelino et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations